SPATIAL ANALYST OF RADAR SPACE IMAGERY IN THE MODULE OF ARCGIS SPATIAL ANALYST - Sh.A. Rahmatov; A.R. Asadov (Journal of new century innovations, 2022)
The article presents several methods of the ARCGIS Spatial Analyst module used to study the surface relief and the results obtained from them. Thematic maps showing the types of relief, their steepness and slope were created from the used methods.